Factors influencing personal financial planning and investment decision: Malaysian scenario - Jalil, Md. Abdul (s.n, 2012)
This research has an intention to develop a research framework grounded on a strong theoretical and literature review background. This study explores the critical factors that influence a financial planning after retirement among Malaysians. The study offers an insight into the financial planning in Malaysia which has somewhat encountered certain limitation in the previous investigation